2019
DOI: 10.1002/jbt.22336
|View full text |Cite
|
Sign up to set email alerts
|

Abamectin induces apoptosis and autophagy by inhibiting reactive oxygen species‐mediated PI3K/AKT signaling in MGC803 cells

Abstract: Abamectin (ABA) is one of the most widely used compounds in agriculture and veterinary medicine. However, the cytotoxicity of ABA in human gastric cells is utterly unknown. In this study, ABA suppressed the proliferation of MGC803 cells by arresting the cell cycle at the G0/G1-phase. Moreover, ABA induced mitochondrialmediated apoptosis by inducing the loss of mitochondrial membrane potential, upregulation of Bax/Bcl-2, and activation of caspase-3. ABA significantly improved the LC3-II/LC3-I ratio and reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Furthermore, we observed that the level of phosphorylated AKT was restored in the NAC-treated group, indicating that ROS is an upstream regulator of PI3K/AKT inactivation in the combined treatment group. Similar to our findings, ROS has also been found to inhibit the PI3K/AKT pathway in various tumor cells treated with natural anti-tumor drugs [46,47].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we observed that the level of phosphorylated AKT was restored in the NAC-treated group, indicating that ROS is an upstream regulator of PI3K/AKT inactivation in the combined treatment group. Similar to our findings, ROS has also been found to inhibit the PI3K/AKT pathway in various tumor cells treated with natural anti-tumor drugs [46,47].…”
Section: Discussionsupporting
confidence: 91%
“…An increase in autophagy that occurs as an adaptation to stress can lead to reduced apoptotic cytotoxicity, whereas abnormal/excessive autophagy can accelerate apoptotic cell death [ 37 , 38 , 39 ]. A large number of studies have found that oxidative stress can induce apoptosis, autophagy, or both, leading to harmful effects on reproductive function [ 40 , 41 ]. In agreement with these results, the findings of the current study revealed the appearance of large numbers of autophagosomes, the gold-standard markers of autophagy, in the allethrin-treated ovaries [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely acknowledged that mTOR, the downstream target of PI3K and AKT, is the core modulator of autophagy because its suppression leads to stimulation of autophagy [ 49 ]. In addition, the inhibition of ROS generation negatively affects apoptosis and autophagy [ 44 ], and ROS-mediated autophagy is associated with inactivation of the PI3K/AKT/mTOR signaling pathway [ 40 , 50 ]. Consistent with our results, a large number of toxicants induce oxidative stress-mediated autophagy by downregulating the PI3K/AKT/mTOR pathway or inhibiting mTOR [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…77,78 Abamectin is known to activate oxidative stress, which can result in an imbalance in antioxidant enzymes such as Superoxide Dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione S-transferase (GST) and the peroxidation product malondialdehyde (MDA). [79][80][81] HSPs function as molecular chaperones by promoting proper protein folding and preventing the aggregation of denatured proteins under stress, which helps cells resist oxidative stress. 76 Therefore, we speculated that the evolutionary adaptation of insects to higher temperatures might be a process that modulates the toxicity of insecticides at higher temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Insecticides can also damage antioxidant systems and may cause oxidative stress, apoptosis and the inhibition of autophagy 77,78 . Abamectin is known to activate oxidative stress, which can result in an imbalance in antioxidant enzymes such as Superoxide Dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione S ‐transferase (GST) and the peroxidation product malondialdehyde (MDA) 79‐81 . HSPs function as molecular chaperones by promoting proper protein folding and preventing the aggregation of denatured proteins under stress, which helps cells resist oxidative stress 76 .…”
Section: Discussionmentioning
confidence: 99%